The 5′UTR variant of ERCC5 fails to influence outcomes in ovarian and lung cancer patients undergoing treatment with platinum-based drugs - Rulli, Eliana (Sci Rep, 2016)
The common polymorphic variant in the 5′ untranslated region of the excision repair cross-complementation group 5 (ERCC5) gene was described to generate an upstream open reading frame that regulates both the basal ERCC5 expression and its ability to be synthesized following DNA damage. This variant was reported to affect response to platinum therapy in a cohort of patients with pediatric ependymoma. The role of this variant was investigated in two cohorts of cancer patients, specifically in non-small-cell lung cancer (NSCLC) patients (N = 137) and in epithelial ovarian carcinoma (EOC) patients (N = 240), treated in first-line with platinum-based compounds. Differently from what reported for pediatric ependymoma, the analysis of the polymorphism in NSCLC patients cohort was not able to detect any difference among patients harboring different genotypes both in progression free survival (HR = 0.93; 95%CI 0.64–1.33; p-value = 0.678) and overall survival (HR = 0.90; 95%CI 0.62–1.33; p-value = 0.625). These data were corroborated in a EOC patients cohort, where similar progression free survival (HR = 0.91; 95% CI 0.67–1.24; p-value = 0.561) and overall survival (HR = 0.98; 95% CI 0.71–1.35; p-value = 0.912) were found for the different genotypes. These data, obtained in appropriately sized populations, indicate that the effect of this ERCC5 polymorphism is likely to be relevant only in specific tumors.